Inter-cultural Mediation in the Prevention of Labor Exploitation and the Sexual Traffic… 155 Inter-cultural Mediation in the Prevention of Labor Exploitation and the Sexual Traffic of Migrant Children and Adolescents - Morales Flores, María de Lourdes; Rivera Varela, Bertha Leticia; Mejía Rubio, Silvia (Trabajo Social UNAM, 2016)
A professional experience implies the emergence of a model of intervention in the face of the changes in mutually inclusive problems including immigration, labor exploitation and human trafficking. In this way a research experience is interwoven with the problem of research and the model of intervention which, from the point of view of Social Work, has been built in order to establish the axes of the necessary discussion, action and jurisprudence for providing social and public safety on matters of Human Development. That is why in the present experience of intervention, axes of debate have been drawn which allow for the implementation of a systemic model of prevention of labor and sexual exploitation of children and adolescent migrants. The objective of the present paper is precisely to describe the experience of intervention in order to establish the axes of Human Development which reveal the importance of Social Work in vulnerable sectors, such as those of migrant communities of children and adolescents who leave Mexico for the United States. In the future, professional experiences will be directed at implementing a program combined with diagnosis of local development, from which it will be possible to establish models of intervention. However, the intervention of Social Work will be better guided by local diagnosis which involves ex profeso models depending on the community being studied and its inherent problems.